O VIZIUNE DOCUMENTARĂ NOUĂ ASUPRA EVOLUŢIEI POLITICILOR DE BIBLIOTECĂ ÎN REPUBLICA MOLDOVA - MARTIN, Doctor în ştiinţe pedagogice, şef secţie marketing şi contracte, ÎS „MoldData", Eugen (BIBLIOPOLIS, 2020)
The research POLICY DEVELOPMENT IN THE NATIONAL LIBRARY SYSTEM OF MOLDOVA prepared by Mariana Harjevschi has a special significance for the development of society, social progress and culture development. It is listed the strengths of the paper - review from the practical knowledge of all policy ele-ments, opinions of experts in the field, but as well the internaţional prospective. It is noted its value for the for policy development of the National System of Libraries and excelency of practical approach, based on solid theoretical foundation related to the defînition ofpolicies of the national libraries, establishing the correlation of library policies and regulatory framework, as well as offering innovative products (ex. model Guidelines for Strategy development on libraries) recommendations on different levels of management libraries to streamline the national policy for libraries.